# What is the product of the radical expression (-5-√3) ^2 ?

### 2 Answers | Add Yours

`(-5-sqrt3)^2`

Squaring an expression is the same as multiplying it 2 times.

`(-5-sqrt3) (-5-sqrt3)`

Now use the FOIL method.

`(-5*-5)(-5*-sqrt3)(-sqrt3*-5)(-sqrt3*-sqrt3)`

Simplify by multiplying and combining like terms.

`(25+10sqrt3+sqrt3^2)`

Raising a square root to the square power results in the expression inside the root.

`25+10sqrt3+3`

Add 3 to 25 to get 28.

`28+10sqrt3`

** `(-5-sqrt3)^2= 28+10sqrt3`**

**Sources:**

(-5-√3)*2*= {-(5+ √3)}2

=(5+ √3) 2

=(5)2+2*5*√3 +(√3)2 [Using formula (a+b)2=a2+2ab+b2]

= 25 + 10√3 + 3

= 28 + 10√3

Hence, (-5-√3)2 = 28 + 10√3 <-- Answer